2018
DOI: 10.1155/2018/5278565
|View full text |Cite
|
Sign up to set email alerts
|

Leader-Follower Based Locally Rigid Formation Control

Abstract: This paper addresses motion control of a cooperative intelligent transport system (C-ITS) of nonholonomic mobile robots navigating a dynamic environment while maintaining a locally rigid formation. We consider the design of acceleration-based control inputs that govern the motion of cooperative intelligent transport system (C-ITS) using the artificial potential fields method for the avoidance of obstacles and attraction to designated targets. The control scheme utilizes a new leader-follower strategy using Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The feedback control laws for the dynamic system is extracted by finding the time derivative of the various components of L (x) along a solution of dynamic system (6) and force it to be at least semi-negative definite. Upon suppressing x, the time derivative of L (x), equation (20) iṡ…”
Section: B Nonlinear Controllersmentioning
confidence: 99%
See 1 more Smart Citation
“…The feedback control laws for the dynamic system is extracted by finding the time derivative of the various components of L (x) along a solution of dynamic system (6) and force it to be at least semi-negative definite. Upon suppressing x, the time derivative of L (x), equation (20) iṡ…”
Section: B Nonlinear Controllersmentioning
confidence: 99%
“…Every bounded solution x(t) in D(L) of (32) converges to:= {x ∈ D(L) : v = w = u = p = q = r = 0} as t → ∞.Proof: Given the Lyapunov-like function L in(20) and its derivativeL in (29), we see thatL ∈ C 1 [D(L), R + ], R + := [0, ∞). Hence L is locally Lipschtiz in x ∈ D(L).…”
mentioning
confidence: 98%
“…From (18), it can be found that the closed dynamics of platoon is influenced by both the state feedback and interaction topology. If the interaction topology is determined in advance and holds during running, many control theories can be used [15][16][17][18][19][20]. Unfortunately, both the dimension and structure of the topological matrix are uncertain in a real environment, which poses a great challenge to synthesize and analyze the platoon control system.…”
Section: Synthesis Of Distributed H ∞ Controllermentioning
confidence: 99%
“…To overcome the drawback of homogeneous state feedback controller, a heterogeneous feedback controller is further designed to ensure string stability of platoons interacted by bidirectional topology in [15,16]. With the leader-follower topology, the collision avoidance ability is further considered in [17].…”
Section: Introductionmentioning
confidence: 99%
“…Path planning of autonomous robots has been an active research area for more than two decades [11], [12], [13]. Path planning attempts to find a short, collision-free path for robots from the starting position towards the predefined ending location [50].…”
Section: Introductionmentioning
confidence: 99%